Growth rate and nutrient limitation as key drivers of extracellular quorum sensing signal molecule accumulation in Pseudomonas aeruginosa. Issue 4 (5th April 2023) - Dubern, Jean-Frédéric; Halliday, Nigel; Cámara, Miguel; Winzer, Klaus; Barrett, David A.; Hardie, Kim R.; Williams, Paul
Abstract : In Pseudomonas aeruginosa, quorum sensing (QS) depends on an interconnected regulatory hierarchy involving the Las, Rhl and Pq s systems, which are collectively responsible for the co-ordinated synthesis of a diverse repertoire of N -acylhomoserine lactones (AHLs) and 2-alkyl-4-quinolones (AQs). Apparent population density-dependent phenomena such as QS may, however, be due to growth rate and/or nutrient exhaustion in batch culture. Using continuous culture, we show that growth rate and population density independently modulate the accumulation of AHLs and AQs such that the highest concentrations are observed at a slow growth rate and high population density. Carbon source (notably succinate), nutrient limitation (C, N, Fe, Mg) or growth at 25 °C generally reduces AHL and AQ levels, except for P and S limitation, which result in substantially higher concentrations of AQs, particularly AQ N -oxides, despite the lower population densities achieved. Principal component analysis indicates that 26 % variation is due to nutrient limitation and a further 30 % is due to growth rate. The formation of N -(3-oxododecanoyl)-l -homoserine lactone (3OC12-HSL) turnover products such as the ring opened form and tetramic acid varies with the limiting nutrient limitation and anaerobiosis. Differential ratios of N -butanoyl-homoserine lactone (C4-HSL), 3OC12-HSL and the AQs as a function of growth environment are clearly apparent. Inactivation of QS by mutation of three key genes required for QS signal synthesis ( lasI, rhlI and pqsA ) substantially increases the concentrations of key substrates from the activated methyl cycle and aromatic amino acid biosynthesis, as well as ATP levels, highlighting the energetic drain that AHL and AQ synthesis and hence QS impose on P. aeruginosa .